Perfil das ONG's ambientalistas atuantes na Baía de Guanabara, 1990-2001, RJ - Mattos, Solange Maria da Silva Nunes (2009)
Over the last ten years we can see that the organized Brazilian civil society has been taking increasingly stronger stands in the discussion, formulation and execution of public policies. This study focused on several non-governmental organizations (NGOs), that comprise a mosaic of assorted institutions endowed with a unique capacity to conduct local actions following the framework of a global perspective. These NGOs are dedicated to environmental issues and have been active in an extremely important and much impacted estuary in the Brazilian state of Rio de Janeiro Guanabara bay. Our findings indicate that the reclamation and/or preservation projects conducted with the participation of these institutions attract volunteers and the attention of the media, enhance the sensitivity of the general population in relation to environmental problems, and contribute to the education of low-income urban communities. This helps shape a more holistic form of relationship between humans and the natural environment, and aids in the configuration of new social actors. These NGOs also give more efficiency to the interventions of public agencies engaged in the recovery of the environmental quality of the ecosystems found in the estuary.